Positive Bank-to-Bank Spillovers - Shakya, Shasta (Journal of Financial and Quantitative Analysis, 2023)
Abstract This paper provides the first evidence of positive bank-to-bank spillovers. I show that geographic linkages between banks that engage in home lending in the same geographic region transmit positive shocks from one bank to another. I exploit shocks to the deposit base of banks located in counties experiencing shale oil booms and show that a nonshocked bank in a nonboom county expands lending more if its linkages have greater exposure to shale booms. Results show that the shock exposure of linkages has a positive impact on home prices of nonboom counties, and nonshocked banks located therein respond with increased lending.